Iron status in women with infertility and controls: a case-control study - Holzer, Iris; Ott, Johannes; Beitl, Klara; Mayrhofer, Daniel; Heinzl, Florian; Ebenbauer, Johanna; Parry, John Preston (Frontiers in Endocrinology, 2023)
Background: Iron deficiency is a common problem in subfertile women. The influence of iron status on unexplained infertility is unknown. Methods: In a prospective case-control study, 36 women with unexplained infertility and 36 healthy non-infertile controls were included. Parameters of iron status including serum ferritin and a serum ferritin <30 µg/dL served as main outcome parameters. Results: Women with unexplained infertility demonstrated a lower transferrin saturation (median 17.3%, IQR 12.7-25.2 versus 23.9%, IQR 15.4-31.6; p= 0.034) and a lower mean corpuscular hemoglobin concentration (median 33.6 g/dL, IQR 33.0-34.1 versus 34.1 g/dL, IQR 33.2-34.7; p= 0.012). Despite the fact that there was no statistically significant difference in median ferritin levels (p= 0.570), women with unexplained infertility had ferritin levels <30µg/L more often (33.3%) than controls (11.1%; p= 0.023). In a multivariate model, unexplained infertility and abnormal thyroid antibodies were associated with ferritin <30µg/L (OR 4.906, 95%CI: 1.181-20.388; p= 0.029 and OR 13.099; 2.382-72.044; p= 0.029, respectively). Conclusion: Iron deficiency with ferritin <30µg/L seems to be associated with unexplained infertility and might be screened in the future.